Association of psychological flexibility with engagement in pulmonary rehabilitation following an acute exacerbation of chronic obstructive pulmonary disease. (30th September 2019) - Fernandes-James, Caroline; Graham, Christopher D; Batterham, Alan M; Harrison, Samantha L
This study aimed to investigate (a) the association between psychological flexibility and engagement in pulmonary rehabilitation within 8 weeks following hospitalisation for an acute exacerbation of chronic obstructive pulmonary disease (AECOPD) and (b) how psychological (in)flexibility presents in this context. A mixed-methods study was conducted. Psychological flexibility during an AECOPD was assessed using The Acceptance and Action Questionnaire-II (AAQ-II) ( n = 41) and the Engaged Living Scale (ELS) ( n = 40). Engagement in post-AECOPD pulmonary rehabilitation was then recorded. Twenty-three patients also participated in cognitive interviews. Psychological flexibility was associated with a greater chance of accepting a pulmonary rehabilitation referral following an AECOPD. Small numbers prohibited analysis on attendance or completion. An AAQ-II score of 11 translated to a 60 (37–82)% probability of accepting a referral to pulmonary rehabilitation and an ELS score of 73 was associated with a 68 (46–91)% probability of accepting. Four themes were extracted from interviews: (1) family values, (2) self as abnormal, (3) 'can't do anything' versus 'I do what I can' and (4) disability, and related emotions, as barriers to action. Randomised clinical trials are needed to evaluate interventions designed to increase psychological flexibility (i.e. acceptance and commitment therapy) to support acceptance of pulmonary rehabilitation post-AECOPD.